Immunotherapy for squamous cell carcinoma of the head and neck. (8th August 2020) - Yokota, Tomoya; Homma, Akihiro; Kiyota, Naomi; Tahara, Makoto; Hanai, Nobuhiro; Asakage, Takahiro; Matsuura, Kazuto; Ogawa, Takenori; Saito, Yuki; Sano, Daisuke; Kodaira, Takeshi; Motegi, Atsushi; et al.
Abstract: Squamous cell carcinoma of the head and neck is characterized by an immunosuppressive environment and evades immune responses through multiple resistance mechanisms. A breakthrough in cancer immunotherapy employing immune checkpoint inhibitors has evolved into a number of clinical trials with antibodies against programmed cell death 1 (PD-1), its ligand PD-L1 and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) for patients with squamous cell carcinoma of the head and neck. CheckMate141 and KEYNOTE-048 were practice-changing randomized phase 3 trials for patients with platinum-refractory and platinum-sensitive recurrent or metastatic squamous cell carcinoma of the head and neck, respectively. Furthermore, many combination therapies using anti-CTLA-4 inhibitors, tyrosine kinase inhibitors and immune accelerators are currently under investigation. Thus, the treatment strategy of recurrent or metastatic squamous cell carcinoma of the head and neck is becoming more heterogeneous and complicated in the new era of individualized medicine. Ongoing trials are investigating immunotherapeutic approaches in the curative setting for locoregionally advanced disease. This review article summarizes knowledge of the role of the immune system in the development and progression of squamous cell carcinoma of the head and neck, and provides a comprehensive overview on the development of immunotherapeutic approaches in both recurrent/metastatic and locoregionally advanced diseases. Abstract : Immune checkpoint inhibitors play a crucial role in the strategy for treating squamous cell carcinoma of the head and neck.